Analysis, conversion and visualization of discrete simulation results - Zhong, Yongmin; Shirinzadeh, B. (IEEE, 2004)
This paper presents a methodology to create 3D visualization of discrete event simulation. This methodology connects discrete event simulation directly to 3D animation with its novel methods of analyzing and converting discrete simulation results into animation events to trigger 3D animation. Discrete simulation results are analyzed and displayed in a graph structure that reveals all possible sequences of simulation events. In addition, a 3D animation framework is constructed for the visualization of discrete simulation results. This framework supports the reuse of both the existing 3D animation objects and behavior components, and allows the rapid development of new 3D animation objects by users with no special knowledge in computer graphics. This methodology has been implemented with the software component technology. Results in an electronics assembly factory are also provided in the paper to demonstrate the feasibility of this approach.